Analisis Peran Program Jaminan Kesehatan Nasional (JKN) dalam Mengurangi Beban Finansial Pasien: Studi Literatur - Cynthianoor Fitriana Puteri Zebua; Ardhila, Diva; Yuriska, Yuriska; Gurning, Fitriani Pramita (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Insurance or coverage is an agreement in which an insurer binds himself to the insured by accepting a premium, to provide compensation to him for losses, damages, or loss of profits that may be suffered due to uncertain events (Commercial Law Book (KUHD) of the Republic of Indonesia Article 246). The interesting thing analyzed is first, the form of protection for workers in the National Health Insurance (JKN) program and second, the issues in its implementation. The model used in this work is a literature review, where information suitable for the problem being investigated is sought from various references and sources. Here is the selection of scientific articles: The selection of scientific articles was done by searching the PubMed, ScienceDirect, and Google Scholar databases for relevant articles published in the period 2019-2023. The selected articles must meet the established inclusion and exclusion criteria. Determination of Inclusion and Exclusion Criteria: The inclusion criteria used in this study include articles on "Analysis of the effectiveness of health insurance in reducing the financial burden of patients" and studies conducted at the provincial or national level. The exclusion criteria are articles that do not meet the inclusion criteria, articles that are not related to the research topic, and articles published before 2019.